Overexpression of CD157 Contributes to Epithelial Ovarian Cancer Progression by Promoting Mesenchymal Differentiation - Morone, Simona; Lo-Buono, Nicola; Parrotta, Rossella; Giacomino, Alice; Nacci, Giulia; Brusco, Alfredo; Larionov, Alexey; Ostano, Paola; Mello-Grand, Maurizia; Chiorino, Giovanna; Ortolan, Erika; Funaro, Ada (PLOS ONE, 2012)
Epithelial ovarian carcinoma (EOC) is an aggressive tumor often diagnosed at an advanced stage, when there is little or no prospect of cure. Despite advances in surgical and chemotherapeutic strategies, only marginal improvements in patient outcome have been obtained. Hence, unraveling the biological mechanisms underpinning EOC progression is critical for improving patients’ survival. Recently, we reported that CD157 (an ectoenzyme regulating leukocyte diapedesis) is expressed in EOC and that high expression of the molecule is negatively correlated with the disease outcome in patients. Here, we demonstrate that forced overexpression of CD157 in OVCAR-3, TOV-21G, A2780 and OV-90 ovarian cancer cell lines promotes morphological and phenotypic changes characterized by disruption of intercellular junctions, downregulation of epithelial markers and upregulation of mesenchymal ones. These changes in cell shape and phenotype bring to reduced sensitivity to anoikis, increased anchorage-independent growth, cell motility and mesothelial invasion. Conversely, knockdown of CD157 in OV-90 and OC314 cells reverts the mesenchymal phenotype and reduces the cells’ migratory potential. Transcriptome profiling analysis highlighted 378 significantly differentially expressed genes, representing the signature of CD157-overexpressing OVCAR-3 and OV-90 cells. The modulation of selected genes translates into alteration of protein expression that give cells a highly malignant phenotype. The overall picture deduced from the analysis of the modulated transcripts is that high expression of CD157 strengthens a number of biological processes favoring tumor progression (including development and cell motility), and weakens several biological processes hindering tumor progression (such as apoptosis, cell death and response to stress). Together, these findings implicate CD157 in the progression of EOC to metastatic disease and suggest that CD157 may represent a valuable therapeutic target.